2015
DOI: 10.1667/rr13928.1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Therapeutic Irradiation on Healthy Articular Cartilage

Abstract: Radiation-induced complications in bone and cartilage are of increasing concern due to potential long-term effects in cancer survivors. Healthy articular cartilage may be exposed to radiation during either chondrosarcoma treatment or in-field radiotherapy of tumors located in close proximity to articulation. Cartilage exposed to radiation undergoes bone differentiation and senescence, which can lead to painful and disabling sequelae that can impair patient quality of life. An understanding of the biological pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 108 publications
1
23
0
Order By: Relevance
“…Monolayer 2D culture of HACs was used as a control. Very few studies have been published on the survival of HACs after IR exposure (6). The data analysis of D 10 survival after X-ray irradiation (4.1 Gy) showed a rather higher value (2.7 Gy) than previously reported (29).…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…Monolayer 2D culture of HACs was used as a control. Very few studies have been published on the survival of HACs after IR exposure (6). The data analysis of D 10 survival after X-ray irradiation (4.1 Gy) showed a rather higher value (2.7 Gy) than previously reported (29).…”
Section: Discussionmentioning
confidence: 70%
“…Depending on the cell lines, it can be triggered by low or very high doses of IR (27). Moreover, human mesenchymal cells (precursors of chondrocytes), in contrast to arthritic chondrocytes, do not undergo radiation-induced apoptosis, probably owing to the efficient activation of the DNA damage response pathways (6,33). Furthermore, our results have shown that C-ion irradiation induced twice as much SA-b-Galepositive cells in 2D culture compared with X-ray irradiation (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(9) The advent of tissue engineering techniques has provided alternative options for treating such patients by using cellular therapy in combination with synthetic extracellular matrix substitutes and biologically active factors for the functional replacement of articular hyaline cartilage. (10) This study showed that the bone matrix granules, when implanted into the articular cartilage defect zone, have a pronounced chondromodulatory effect, prolonged by activating reparative chondrogenesis. In the area of damage to the articular cartilage in the early period, a regenerate is formed, acquiring the cellular specificity of the hyaline cartilaginous tissue.…”
Section: Discussionmentioning
confidence: 79%